Greek and Roman Slaveries - Bathrellou, Eftychia; Vlassopoulos, Kōstas (Wiley-Blackwell, 2022)
Greek and Roman Slaveries Slavery was foundational to Greek and Roman societies, affecting nearly all of their economic, social, political, and cultural practices. Greek and Roman Slaveries offers a rich collection of literary, epigraphic, papyrological, and archaeological sources, including many unfamiliar ones. This sourcebook ranges chronologically from the archaic period to late antiquity, covering the whole of the Mediterranean, the Near East, and temperate Europe. Readers will find an interactive and user-friendly engagement with past scholarship and new research agendas that focuses particularly on the agency of ancient slaves, the processes in which slavery was inscribed, the changing history of slavery in antiquity, and the comparative study of ancient slaveries. Perfect for undergraduate and graduate students taking courses on ancient slavery, as well as courses on slavery more generally, this sourcebook's questions, cross-references, and bibliographies encourage an analytical and interactive approach to the various economic, social, and political processes and contexts in which slavery was employed while acknowledging the agency of enslaved persons.